FIGURES 48–56 in On the genus Mannerheimia Mäklin, 1880 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini), with taxonomic and faunistic notes on some species - Shavrin, Alexey V. (Zenodo, 2021)
FIGURES 48–56. Aedeagus of Mannerheimia brevipennis (48–49: Kazakhstan: Aksu, 50: Krasnoyarsk Territory: Turukhanskiy District, 51: Buryatia: Okinskiy District, 52: Yamal: Sopkey; 53: Kyrgyzstan: Ala Too; 54: Yakutia: Spasskiy; 55: Iran: Esfahan; 56: China: Xinjiang): 48, 50–56—parameral view, 49—lateral view. Scale bar: 0.1 mm. : Published as part of Shavrin, Alexey V., 2021, On the genus Mannerheimia Mäklin, 1880 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini), with taxonomic and faunistic notes on some species, pp. 301-333 in Zootaxa 5040 (3) on page 318, DOI: 10.11646/zootaxa.5040.3.1, http://zenodo.org/record/5531372